POSITIONING DAN FAKTOR-FAKTOR YANG MEMPENGARUHI LOYALITAS KONSUMEN DALAM MEMILIH PRODUK MIE INSTAN DALAM KEMASAN DI JAKARTA - Fahrul Riza (Business Management Journal, 2017)
The advance in food technology and the effort from producer to fulfill the need of customers, have had produces a wide variety of products. Each of these products competes in the market to grab the attention of consumers. For example is the instant noodle product in packaging. There are currently fifty brands of instant noodle in packaging with variety of flavours and sizes.Buying instant noodle products is classified to low involvement process. This research will discuss what factors determine brand loyalty, as well as mapping the posisition of each brand in the market today in a map of perceptions.The results of calculation by using the regression analysis showed distribution, brand awareness, and brand image are the main determining factors of brand loyalty.To win the competition, the manufacturer should always put on a marketing strategy that includes: accessible on the stalls or shops nearby (availability), good quality products and brand well known or popular among consumers (acceptability), determination of price range, should be proper to consumers affordability, memorable but not cheap (affordability).Keywords : positioning, loyalitas merk, peta persepsi, low involvement.